Improvement of Video Measuring Systems for Electric Traction Network Diagnostics - Domanskyi, I. V; Vasenko, V. O (Science and Transport Progress, 2021)
Purpose. The purpose of the article is system analysis of the state of electric traction networks, as well as methods of complex diagnostics of the contact network from a moving laboratory car to increase the resolution capability of the systems for monitoring the quality of interaction between the contact network and current collectors. Methodology. The problem was solved by theoretical analysis and experimental studies of the current collection parameters, a generalized model of the device for monitoring the wear of the overhead wire and its functional units in order to determine the factors affecting the control error, as well as the development of methods that reduce the specified error. The apparatus of factor analysis, the theory of optoelectronic circuits and methods of statistical information processing were used. Findings. Innovative approaches and qualitatively new diagnostic tools are proposed that allow expanding the functionality of the laboratory cars for testing the contact network for power supply enterprises of electrified railways, industrial and urban electric transport. Hardware and software have been developed to improve the system for measuring the parameters of the overhead wire and other components of the contact network. Originality. The theoretical maximum permissible, from the point of view of the contact network operation, error in monitoring the wear of the overhead wire and other components of the electric traction network has been determined. A method for increasing the resolution capability of a stereo television system and an adaptive lighting system is proposed. It consists in preliminary image transformation and expansion of the dynamic range of image measurement. The ways of introducing a high-speed real-time compression algorithm and using LED backlighting are proposed. Practical value. The quality of the contact network diagnostics in difficult conditions for video surveillance has been improved. A camera with a built-in image compression module without losing its performance is proposed, which allows capturing and transmitting full-frame images to a computing complex for the application of new diagnostic algorithms for contact network components. The modernized video measuring systems for the wear of the overhead wire for monitoring the grounding of the contact network supports are proposed, as well as elements of track facilities located in the visibility zone of specialized cameras, which ensure the operability of the systems at any time of the day at speeds up to 160 km/h. An air curtain subsystem was implemented to protect the cameras.